Data Conveyance Maximization in Bilateral Relay System using Optimal Time Assignment - Chen, Joy Iong Zong; Lai, Kong-Long (Journal of Ubiquitous Computing and Communication Technologies, 2020)
The paper puts forward an optimal time assignment for the bilateral relay system in order to heighten the total amount of data conveyed through it. To have an optimal time assignment the conveyance rate of the two way transmission is obtained using the successful conveyance probability and the destined data rate. Taking into consideration the acquired particulars of data conveyance the paper has proposed an optimal time assignment for every connection. The results observed on evaluating the performance proved that the bilateral relay system with the optimal time assignments has improved the coverage, reliability and the throughput of the wireless communication system.
Keywords: Wireless Communication System; Bilateral Relay System; Data Conveyance Rate; Optimal Time Assignment; Performance Improvement